An annotated checklist of Coleoptera (Insecta) from the island of Crete, Greece - Chatzimanolis, Stylianos; Bolanakis, Giannis; Dedovic, Tarik; Hankins, Kath-Ryn Ann F.; Pavlou, Christoforos; Trichas, Apostolos (Zootaxa, 2026)
We provide, for the first time, an annotated checklist of the beetle fauna of Crete, Greece. We present an overview of the coleopterological history of Crete, along with background information of the physical attributes of the island. Data for the checklist were extracted from the collection of the Natural History Museum of Crete, GBIF, Fauna Europaea, the Catalogue of Palaearctic Coleoptera and various revisions. We report 2201 unique taxa (species or subspecies) belonging to 63 families. We also report 355 taxa as endemic to Crete or the surrounding islets, and 48 taxa as adventive to Crete. Fourteen new species records are reported, two for Buprestidae, two for Histeridae (including a new record for Greece), one for Oedemeridae (including a new record for Greece) and nine for Scarabaeidae. We compare the beetle fauna of Crete with the beetle fauna of Cyprus, Malta, and Sardinia within the Mediterranean Sea. Additionally, we provide comparisons with the California Channel Islands, the Canary Islands, the Galapagos Islands and the Socotra Archipelago.